Des/obediência na de/colonialidade da formação docente em arte na América Latina (Brasil/Colômbia) - Eduardo Junio Santos Moura (2018)
In this thesis I question the thought under the modern/colonial prism reflecting on the possibilities and impossibilities of decoloniality of Latin American artistic/educational thought. The focus is on the initial and academic Art teacher training in Latin America starting from the hypothesis that it privileges the Eurocentric matrix knowledge. This assumption considers the colonial marks, wounds and legacies of a Latin America that has repercussions in teaching training courses/programs, in the curricula and in the formative processes for teaching Art. The hegemony of this matrix knowledge has made Art teaching/learning to have little or no sense/meaning for the knowledge of Latin American realities (artistic, cultural, social, political, historical) and produce a colonial Art/Education that reveals a unique history: European/American, which is a consequence of a notably reproductive uncritical and apolitical teacher training. The hierarchization and invisibilization of other arts, cultures and histories prevent the teaching formation by other epistemes and forms to think that, in the decolonial perspective that I defend, it goes through the legitimation of Latin American knowledge, art and culture. Thus, I question the constitutive processes of teacher education in Art in Latin American contexts, specifically in Brazil and Colombia, in order to analyze the elements that are considered obedience that maintain coloniality and as disobedience that enable the decoloniality of training processes. Thus, I analyzed the curricula of two Art courses and initial teacher training program in in two universities, one Brazilian and one Colombian. I also conversed with formation teachers and undergraduate students in these universities in order to identify elements of obedience and disobedience to Eurocentric hegemony in ways of thinking and training teachers in Latin American contexts. Such disobedience implies thinking /making a decolonial teacher training which legitimates knowledge from the Latin American art and culture. I find in the Latin American intellectuals thinking (Darcy Ribeiro, Paulo Freire, Ana Mae Barbosa, Rita Segato) and especially of the group Modernity/Coloniality (Aníbal Quijano, Enrique Dussel, Immanuel Wallerstein, Fernando Coronil, Walter Mignolo, Catherine Walsh, Nelson Maldonado-Torres, Silvia Rivera Cusiquanqui, Arturo Escobar, Santiago Castro-Gómez, Edgardo Lander), the decolonial perspective to (re)think critically the artistic/educational realities of Latin America. Hence, I relate the thought of these intellectuals to Art, Education and the initial formation of Art teachers in order to oppose the great eurocentric modernist narratives by thinking disobedience in the decoloniality of the formative processes as a perspective to reflect a decolonial Art/Education that contributes to the recognition of who we are, as an opportunity of collectively stop being what we are not.